DAMPAK FLUKTUASI HARGA MINYAK DUNIA TERHADAP EKONOMI DI INDONESIA - Soesanto, Edy; Utami, Puspita Dewi; Salsabillah, Anjani; Refangga, Bagus Hery (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Referring to the significance of the energy sector in the national economy, changes in global oil prices have a significant impact on the raw materials economy in Indonesia. This research aims to explore the influence of international oil price fluctuations on the oil and gas sector, investment in the energy sector, and state income. The methods applied include qualitative and quantitative approaches to assess these impacts, including analysis of historical data regarding global oil prices, domestic energy production patterns, and energy policies implemented by the government. The study results show that global oil price fluctuations not only affect government revenues from the oil and gas sector, but also pose challenges to investment sustainability, energy diversification and economic stability. Indonesia's dependence on petroleum as its main energy source makes it vulnerable to changes in international markets. Therefore, adaptive actions are needed, such as increasing energy efficiency, accelerating the development of renewable energy, and strengthening economic diversification based on natural resources. This study presents strategic recommendations to minimize the negative impact of global oil price fluctuations on the national economy, with an emphasis on strengthening energy policy and optimizing the potential of other natural resources. This research also emphasizes the importance of collaboration between the public and private sectors in facing these challenges.